Numerical simulation and fire experiment in residential dormitory - Tabaczenski, Roberta; Corrêa, Cristiano; Pires, Tiago Ancelmo; Rêgo e Silva, José Jéferson (Revista ALCONPAT, 2018)
This article presents a computer-made simulation of a fire that had already been done by experiment in a room that reproduced a bedroom of a one-family residence, typically burned in the city of Recife (Pernambuco - Brazil). The experimental test of this fire has been presented by Corrêa et al. (2017), and the study presented in this article has as objective to compare the results on the development of the temperature of gases, got from the computer-made simulation with the software Fire Dynamics Simulator (FDS) with the values got by the experiment. We have found out that the temperature obtained through the model developed by the FDS were coherent with the ones obtained by experiment. We hope this study shall help and encourage this tool’s use in studies about Buildings’ Fire Prevention (BFP) in rooms and fire in residences.